Debris based discharge segregation in reverse micro EDM. (1st March 2020) - Roy, T.; Datta, D.; Balasubramaniam, R.
Highlights: Segregation of discharges in reverse micro EDM with increase in machining time. The number of secondary and higher order discharges increases with time. Lower size of agglomerated debris required for full discharge at reduced OCV. Abstract: Segregation of discharge pulses in micro electrical discharge machining (MEDM) and its variants viz. wire EDM, reverse micro EDM (RMEDM) etc. is mostly carried out on the basis of voltage and current signals. With increase in the machining time, more and more debris accumulate thereby causing abnormal discharges which degrades the machining process. This paper attempts to model discharges in the presence of debris, which hitherto has not been established in literature. Two different simulations were carried out (a) to segregate discharges based on electric field intensity in the presence or absence of debris and (b) to determine the minimum size of debris agglomeration required for a full discharge at increasing machining time where open circuit voltage (OCV) reduces. Based on the magnitude of electric field intensity, the discharge pulses are segregated into three stages: primary or normal discharge without debris, secondary discharge with singular debris particles and higher order discharge in the presence of debris agglomerates. Segregation of discharge pulses in case of experiments is done based on magnitude of voltage which shows that primary discharges dominate initially, however, with increase of machining time, the number of secondary and higher order discharges increase as compared to the primary discharges. A good agreement was established between simulation (segregation of discharges based on magnitude of electric field intensity) and experiments (segregation of discharges based on magnitude of voltage). Moreover, to initiate a full discharge at reduced OCV (higher machining time), a higher size of agglomerated debris is required as compared to the case with rated OCV; wherein full discharge occurs in the absence of debris. The size of agglomerated debris required for initiating a full discharge at lower OCV is very small as compared to the size of actual agglomerated debris, thereby, confirming that number of primary discharges are comparatively lower than the secondary or higher order discharges at higher machining time.